Sosialisasi Hadits tentang Kebersihan Lingkungan di Pondok Pesantren Al-Hayatul Islamiyah Kota Malang - Nurcholiq, Mochamad; Riza Maulidia (Ngabekti: Jurnal Pengabdian kepada Masyarakat, 2024)
Abstract This devotion is based on the phenomenon of low knowledge and understanding of religious foundations regarding environmental cleanliness. The target of this activity is students who live in Islamic boarding schools. The aim of this activity is to change the environmental conditions of Islamic boarding schools towards a clean and orderly environment. The methods used in this service include outreach and demonstration. First, analyze the conditions in the Islamic boarding school environment when community service is carried out. Second, socialization and delivery of material about hadiths related to environmental cleanliness. Third, the internalization stage and implications of hadith socialization activities regarding environmental cleanliness. The result of this service is to create a clean Islamic boarding school environment which begins with increasing the knowledge and understanding of the Islamic boarding school community regarding the rules or guidelines. The level of knowledge and understanding of the guidelines will be applied if accompanied by assistance and approach. Keywords: environmental cleanliness, islamic boarding school, socialization. Abstrak Pengabdian ini dilatarbelakangi oleh fenomena rendahnya pengetahuan dan pemahaman yayasan keagamaan mengenai kebersihan lingkungan. Sasaran kegiatan ini adalah para santri yang tinggal di pesantren. Tujuan dari kegiatan ini adalah untuk mengubah kondisi lingkungan pesantren menuju lingkungan yang bersih dan tertib. Metode yang digunakan dalam pengabdian ini adalah sosialisasi dan demonstrasi. Pertama, menganalisis kondisi lingkungan pesantren pada saat dilakukan pengabdian masyarakat. Kedua, sosialisasi dan penyampaian materi tentang hadis terkait kebersihan lingkungan. Ketiga, tahap internalisasi dan implikasi kegiatan sosialisasi hadis mengenai kebersihan lingkungan. Hasil dari pengabdian ini adalah terciptanya lingkungan pesantren bersih yang diawali dengan peningkatan pengetahuan dan pemahaman civitas pesantren mengenai aturan atau pedoman. Tingkat pengetahuan dan pemahaman terhadap pedoman akan diterapkan jika dibarengi dengan pendampingan dan pendekatan. Kata Kunci: kebersihan lingkungan, pondok pesantren, sosialisasi.